Ab Initio and Raman Study of Medium Range Ordering in GeSe2 Glass - Akalın, Elif; Holomb, R.; Mitsa, V.; Sichka, M.; AKYÜZ, SEVİM (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2013)
High resolution Raman spectra of GeSe2 glass were measured and fitted using individual Gaussian components. The structural origin of the components were interpreted using the results of ab initio density functional theory calculations performed on GenSem nanoclusters (n = 2-6, 12; m = 6-9, 12, 14-16, 30) which represent the local structure of GeSe2 glass and on some "defect" GenSem clusters that are thought to be related to the inhomogeneity of the structure at the nanoscale. The calculated vibrational properties of GenSem nanoclusters and their couplings with the short- and medium-range order structure formations in GeSe2 glass are analyzed and discussed. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Ab Initio; DFT; finite nanoclusters; GeSe2 glass; raman spectra; nonlinear-optical properties; chalcogenide glasses; crystal-structure; germanium selenide; amorphous-semiconductors; molecular-dynamics; gexse1-x glasses; random network; liquid gese2; sonlu nanoklusters; GeSe2 cam; raman spektrumu; doğrusal olmayan optik özellikler; kalsiyojenür camları; kristal yapı; germanyum selenit; Amorf-yarıiletken; moleküler dinamik; rasgele ağ